The Epley maneuver for benign paroxysmal positional vertigo: A review of the literature - Santos, José Agostinho (2012)
Goal: The objective of this study is to review the evidence on the efficacy and safety of the Epley maneuver (EM) in the treatment of posterior canal benign paroxysmal positional vertigo (BPPV). Data sources: Medline, evidence-based medicine websites, the Index of Portuguese Medical Journals, and references of selected arti- cles. Review methods: Guidelines, systematic reviews, meta-analyses and randomized controlled trials using the MeSH terms benign pa- roxysmal positional vertigo and therapy. The Strength of Recommendation Taxonomy (SORT) was used for the assignment of levels of evidence and the strength of recommendations. Results: The American Academy of Neurology reports that the EM is effective and safe and is a treatment option for any patient with posterior BPPV. The American Academy of Otolaryngology recommends that the EM be used as first line treatment for BPPV. A Coch- rane meta-analysis (level of evidence 1) found the EM better than placebo treatment and no treatment for symptoms (OR = 4.42) and for producing a negative Dix-Hallpike (DH) test (OR = 6.40). The meta-analysis by Prim-Espada found that patients undergoing the EM had better resolution of symptoms (OR = 6.52) (level of evidence 2). Helminski's systematic review found a higher rate of ne- gative DH tests in the treated groups (67 - 93%) compared to control groups (10 - 38%) (level of evidence 3). Serious side effects were not reported (level of evidence 1). Conclusions: The evidence reveals that the EM is effective and safe in the treatment of BPPV in the short term (SOR A). The EM is of great value to the General Practitioner in the rapid resolution of posterior BPPV without major side effects and without great costs.